Multi-color fluorescence of pNIPAM-Based nanogels modulated by dual stimuli-responsive FRET processes. (October 2017) - Lee, Seung Hwan; Bui, Hoa Thi; Vales, Temmy Pegarro; Cho, Sung; Kim, Ho-Joong
Abstract: We report the modulation of the dual photo/thermo-responsive multicolor fluorescence from poly( N -isopropyl acrylate) pNIPAM-based nanogels. The thermo-responsive pNIPAM-crosslinked matrix was covalently copolymerized with nitrobenzoxadiazole (NBD) monomers as a Förster resonance energy transfer (FRET) donor and electrostatically conjugated with photochromic spiropyran (SP) dyes as a FRET acceptor. The pristine nanogel emits green fluorescence derived from the NBD moieties; however, the irradiation of the nanogels with UV light led to the transformation of the ring-closed colorless SP moieties to the ring-opened coral-red merocyanine (MC) moieties, resulting in light-pink fluorescent nanogels. Notably, at higher temperatures, the fluorescence of the nanogels was red-shifted and enhanced by the more efficient FRET process. The nanogels were well-distributed in the cellular cytoplasm and showed excellent photochromic function in the subcellular environment for applications as photo-switchable bio-imaging agents and nanothermometers. Graphical abstract: Highlights: Selective fluorescence intensity of the nanogels was modulated by thermo-responsive FRET processes. Multicolor fluorescent nanogels consist of nitrobenzoxadiazole and spiropyran dyes. Nanogels showed a photochromic property upon specific light irradiations.